Letter from Robert S. Mulliken to J. Bousquet - Mulliken, Robert Sanderson (1938)
Concerns modifications to the International Table of Isotopes for 1939.
Keywords: Isotopes; Aston, Francis William, 1877-1945; Mulliken, Robert Sanderson; International Union of Pure and Applied Chemistry; Lutetium; Dempster, Arthur Jeffrey; Nobel Prize winners